CLINICAL AND DIAGNOSTIC INSIGHTS INTO HYPOTHYROIDISM IN A SHIH-TZU – A CASE REPORT - H.V. Sanjay; S.P. Abhijith; H.J. Apoorva; D. Chandrakumar; A. Abdul Kalam (Indian Journal of Veterinary and Animal Sciences Research, 2026)
Hypothyroidism in dogs is a common endocrine disorder resulting from deficient thyroid hormone production, leading to a reduced metabolic rate. A four- year-old, neutered female Shih Tzu was presented with a history of progressive weight gain, lethargy, bilateral symmetrical alopecia, and cold intolerance over the preceding three months. Physical examination revealed a dull coat, seborrhoeic dermatitis, bradycardia and mild obesity. Routine haematology and serum biochemistry were within normal limits except for mild hypercholesterolaemia. Thyroid function testing demonstrated low total thyroxine (T4) and free T4 levels with elevated thyroid-stimulating hormone (TSH), confirming primary hypothyroidism. The dog was treated with oral levothyroxine sodium at 20 µg/kg twice daily, resulting in significant clinical improvement within six weeks.